Feasibility Analysis of Sumedang Tofu MSMEs Business with Its Development Strategy - Devi Puspita Sari; Miranda Miranda (Journal of Economics Business Industry, 2023)
This research concerns the development strategy and business feasibility analysis using a value engineering approach. MSMEs Sumedang Tofu is a small industry that processes and markets Sumedang Tofu to the public. The problem that occurs in the sumedang tofu production is environmental conditions that are poorly maintained, and the results of tofu sales fluctuate. Therefore, it is necessary to do a business feasibility analysis to find out whether the Crispy Sumedang Tofu UKM is feasible or not to operate. After identifying the business feasibility analysis aspects, the next step is to determine the right development strategy using a value engineering approach. Value engineering aims to achieve the best value by defining the functions needed to complete the target value and to innovate, improve, and minimize production costs while maintaining the quality and usability of the products produced by considering consumer needs. The development that will be carried out is sumedang crispy tofu packaging. Value engineering has several stages, including information, functional analysis, creative, analysis and evaluation, and recommendations. The Net Present Value (NPV) shows cash flow for three years with a bank interest of 10%, and the resulting NPV is positive. The Internal Rate of Return (IRR) shows that the total value of IRR is 46%, and UKM Sumedang Crispy Tahu is said to be feasible. This is because the IRR value exceeds the loan interest (10%), 46%. and the Payback Period (PP). This MSMEs is feasible to continue because the business capital invested is IDR 143,202,000 and will be fully recoverable within one year and 11 months.